Potential denitrification stimulated by water-soluble organic carbon from plant residues during initial decomposition. (August 2020) - Surey, Ronny; Schimpf, Corinna M.; Sauheitl, Leopold; Mueller, Carsten W.; Rummel, Pauline S.; Dittert, Klaus; Kaiser, Klaus; Böttcher, Jürgen; Mikutta, Robert
Abstract: Denitrification usually takes place under anoxic conditions and over short periods of time, and depends on readily available nitrate and carbon sources. Variations in CO2 and N2 O emissions associated with plant residues have mainly been explained by differences in their decomposability. A factor rarely considered so far is water-extractable organic matter (WEOM) released to the soil during residue decomposition. Here, we examined the potential effect of plant residues on denitrification with special emphasis on WEOM. A range of fresh and leached plant residues was characterized by elemental analyses, 13 C-NMR spectroscopy, and extraction with ultrapure water. The obtained solutions were analyzed for the concentrations of organic carbon (OC) and organic nitrogen (ON), and by UV-VIS spectroscopy. To test the potential denitrification induced by plant residues or three different OM solutions, these carbon sources were added to soil suspensions and incubated for 24 h at 20 °C in the dark under anoxic conditions; KNO3 was added to ensure unlimited nitrate supply. Evolving N2 O and CO2 were analyzed by gas chromatography, and acetylene inhibition was used to determine denitrification and its product ratio. The production of all gases, as well as the molar (N2 O + N2 )–N/CO2 –C ratio, was directly related to the water-extractable OC (WEOC) content of the plant residues, and the WEOC increased with carboxylic/carbonyl C and decreasing OC/ON ratio of the plant residues. Incubation of OM solutions revealed that the molar (N2 O + N2 )–N/CO2 –C ratio and share of N2 O are influenced by the WEOM's chemical composition. In conclusion, our results emphasize the potential of WEOM in largely undecomposed plant residues to support short-term denitrification activity in a typical ˈhot spot–hot momentˈ situation. Highlights: Potential denitrification is closely related to water-soluble OC in plant residues. Amount of water-soluble OC depends on the residue's chemical composition. Chemical composition of water-soluble OM controls the molar (N2 O + N2 )–N/CO2 –C ratio.